2010
DOI: 10.1158/1078-0432.ccr-09-1623
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Inhibition Does Not Improve the Reduction in Ductal Carcinoma In situ Proliferation with Aromatase Inhibitor Therapy: Results of the ERISAC Randomized Placebo-Controlled Trial

Abstract: Purpose: Tamoxifen reduces risk of recurrence after breast conservation surgery for ductal carcinoma in situ (DCIS), but no data exists on the effectiveness of aromatase inhibitors for DCIS. Cyclooxygenase-2 (COX-2) is overexpressed in DCIS, representing another potential therapeutic target. The aim of the study was to determine the effect of aromatase and/or COX-2 inhibition on epithelial proliferation and apoptosis in a presurgical study of estrogen receptor (ER)-positive DCIS.Methods: Postmenopausal women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 17 publications
2
29
0
Order By: Relevance
“…As expected analysis of the no treatment arm showed no significant change in Ki67 or apoptosis during the course of the study in keeping with previous observations [44,45] Our data revealed that there was a non-significant trend towards a reduced level of Ki67 with the celecoxib arm c. 20%. Ki67 at baseline showed no association with response to celecoxib.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As expected analysis of the no treatment arm showed no significant change in Ki67 or apoptosis during the course of the study in keeping with previous observations [44,45] Our data revealed that there was a non-significant trend towards a reduced level of Ki67 with the celecoxib arm c. 20%. Ki67 at baseline showed no association with response to celecoxib.…”
Section: Discussionsupporting
confidence: 92%
“…For instance this study was powered to detect a large effect (≥50%) and any effect of COX-2 inhibition appears to be smaller than this and would require larger patient numbers to detect with confidence. The trend towards a reduction in Ki67 after celecoxib merits further investigation given the potenial importance of confirmation; particularly in view of the fact that previous studies addressing the role of celecoxib on Ki67 in ER+ DCIS [45] and in women with early stage breast cancer [46] have provided conflicting results. For instance in the recent study by Bundred et al, [45] celecoxib had no significant effect on Ki67 when given as a single agent whilst in the Tfayli et al [46] study a significant increase in Ki67 (p<0.009) in response to treatment was noted.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, all these studies showed a correlation between Ki-67 level after treatment and disease-free survival. Also presurgical exemestane treatment modulates Ki-67 and this correlates with the clinical response (27)(28)(29). However, the Ki-67 values are not easily comparable among studies due to the technical variability between different laboratories (30).…”
Section: Discussionmentioning
confidence: 99%
“…At baseline, the median level of Ki-67 was 22% (IQR [16][17][18][19][20][21][22][23][24][25][26][27] in the exemestane group and 18% in the celecoxib and placebo arms (IQR 12-22 and 15-25, respectively). After 6 weeks of treatment, a significant absolute reduction in Ki-67 of 10% (IQR À18 to À5), and over a 50 % relative reduction from baseline was observed in the exemestane group, whereas no change was observed in the two other arms (P value ¼ 0.002 for any treatment versus placebo and P value < 0.0001 for exemestane vs. celecoxib).…”
Section: Tissue Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation